Probiotic Activity of Saccharomyces cerevisiae var. boulardii Against Human Pathogens - Katarzyna Rajkowska; Alina Kunicka-Styczyńska (Food Technology and Biotechnology, 2012)
Infectious diarrhoea is associated with a modification of the intestinal microflora and colonization of pathogenic bacteria. Tests were performed for seven probiotic yeast strains of Saccharomyces cerevisiae var. boulardii, designated for the prevention and treatment of diarrhoea. To check their possible effectiveness against diarrhoea of different etiologies, the activity against a variety of human pathogenic or opportunistic bacteria was investigated in vitro. In mixed cultures with S. cerevisiae var. boulardii, a statistically significant reduction was observed in the number of cells of Listeria monocytogenes, Pseudomonas aeruginosa and Staphylococcus aureus, by even 55.9 % in the case of L. monocytogenes compared with bacterial monocultures. The influence of yeasts was mostly associated with the shortening of the bacterial lag phase duration, more rapid achievement of the maximum growth rates, and a decrease by 4.4–57.1 % (L. monocytogenes, P. aeruginosa), or an increase by 1.4–70.6 % (Escherichia coli, Enterococcus faecalis, Salmonella Typhimurium) in the exponential growth rates. Another issue included in the research was the ability of S. cerevisiae var. boulardii to bind pathogenic bacteria to its cell surface. Yeasts have shown binding capacity of E. coli, S. Typhimurium and additionally of S. aureus, Campylobacter jejuni and E. faecalis. However, no adhesion of L. monocytogenes and P. aeruginosa to the yeast cell wall was noted. The probiotic activity of S. cerevisiae var. boulardii against human pathogens is related to a decrease in the number of viable and active cells of bacteria and the binding capacity of yeasts. These processes may limit bacterial invasiveness and prevent bacterial adherence and translocation in the human intestines.